Bunch length diagnostics with coherent relativistic electron radiation - Ayzatsky, M.I.; Khodak, I.V.; Kushnir, V.A.; Mitrochenko, V.V.; Opanasenko, A.N.; Stepin, D.L. (Вопросы атомной науки и техники, 2001)
One of the most important problems when designing resonance electron linacs with a high beam brightness is creation of an equipment for electron bunch length diagnostics. One of ways to solve this problem is based on analysis of radiation from relativistic electrons (transition, synchrotron etc.). The paper presents results of calculations and experiments on studying the millimeter-band radiation that is a beam exited on the surface of the grating periodic structure and in a linac beam pipe. Experiments were carried out on the linac LIC with 13 MeV particle energy and 0.8 A pulse beam current. The possibility of observed radiation application for estimation of the bunch length value, monitoring its variation and for optimization of the accelerator operating mode was shown experimentally.